Volume collapse phase transitions in cerium-praseodymium alloys under high pressure. Issue 3 (3rd July 2018) - Perreault, Christopher S.; Velisavljevic, Nenad; Samudrala, Gopi K.; Kalai Selvan, G.; Vohra, Yogesh K.
ABSTRACT: Cerium-12at%Praseodymium(Ce0.88 Pr0.12 ) and Ce-50at%Praseodymium(Ce0.50 Pr0.50 ) alloy samples that contain a random solid-solution of Ce ( 4f 1 (J = 5/2)) and Pr ( 4f 2 (J = 4)) localized f -states have been studied by angle dispersive x-ray diffraction in a diamond anvil cell to a pressure of 65 GPa and 150 GPa respectively using a synchrotron source. Ce0.88 Pr0.12 alloy crystallizes in a face-centered cubic ( γ -phase) structure at ambient conditions, while Ce0.50 Pr0.50 alloy crystallizes in the double hexagonal close packed ( dhcp ) structure at ambient conditions. Two distinct volume collapse transitions are observed in Ce0.88 Pr0.12 alloy at 1.5 GPa and 18 GPa with volume change of 8.5% and 3% respectively. In contrast, Ce0.50 Pr0.50 alloy shows only a single volume collapse of 5.6% at 20 GPa on phase transformation to α-Uranium structure under high pressure. Electrical transport measurements under high pressure show anomalies in electrical resistance at phase transitions for both compositions of this alloy.